Increasing Productivity by Empowering Individuals with Mental Illnesses - Warih Andan Puspitosari; Tesaviani Kusumawastiwi; Hilmi Habibi (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
Mental illnesses are the primary cause of lost productivity. People with mental problems have a deterioration in practically all functions as a result of their symptoms, which lowers productivity. Medication by itself won't bring productivity back; initiatives to empower and support people are also required. The activity's goal is to help those who suffer from mental illnesses become more productive. Forming support groups and providing business mentoring are two aspects of the activity approach known as mentoring. Thirteen participants suffered from mental illnesses. Activities for the support group take place across two sessions. Participants receive business capital in the form of hens, cooking supplies, and necessities for a basic food stall based on their ability. team that provides mental health services to the community. The effectiveness of the mentoring activity is assessed by measuring productivity both before and after the engagement. The rise in constructive activities that individuals engage in is used to measure productivity. After helping those with mental health issues and their families in Argodadi Village, Sedayu sub-district, Bantul district, DI Yogyakarta, community service was implemented, and the end result was that all participants actively participated in mentoring activities. The productivity of individuals with mental illnesses is increased when they receive mentoring for themselves and their family. The activity results in research studies published in national journals, media publications, video programs, and dementia modules. The activity results in research studies published in national journals, media outlets, program videos, and the Dementia Module.